Amplification of Microsatellites in the Persian Sturgeon (Acipenser Persicus) - Mogim, M.; Heist, E. J.; Tan, Soon Guan; Pourkazemi, Mohammad; Siraj, Siti Shapor; Panandam, Jothi Malar (2009)
Persian sturgeon (Acipenser persicus) is a benthic species occurring primarily on sandy bottoms in the mid and southern Caspian Sea, especially along the shores of Iran (Berg, 1948; Holcik, 1989). The Persian sturgeon in the Caspian Sea is anadromous, with at least eighteen groups that segregate spatially and temporally for spawning. These populations are supported by some spawners, each of which considered to be of two seasonal races and divided into two or four biological groups (Perevaryukha, 2001).